PENGARUH PENERAPAN ETIKA BISNIS TERHADAP KEPUASAN ANGGOTA BMT DI KECAMATAN PUCAKWANGI - Tuti' Nadhifah; M Adhitya Wardhana (Universitas Muhammadiyah Kudus, 2023)
AbstractBusiness ethics is a knowledge of norms in managing business and morality that apply universally, economically and socially. In the business world, the science of ethics is a very important element, because knowledge covers various aspects, including aspects of the individual, company and society. This research was conducted with the aim of knowing the effect of applying business ethics on the satisfaction of BMT members in Pucakwangi District. The data collection method used in this research is the type of research is field research. In this study, researchers used a descriptive qualitative research approach. Data collection techniques that will be used by researchers in research using interview techniques (interviews), observation, and documentation of BMT members in Pucalwangi District. The results of this study indicate that service quality has a significant influence on the decision making of members or customers in using BMT financial services in Pucakwangi District. In addition to service quality, Islamic business ethics also has a significant influence on the decisions of members or customers in using BMT Pucakwangi District financial services. This is because service quality and business ethics are one of the dominant variables in Member or Customer decisions in choosing BMT financial services in Pucakwangi District. Keywords: Business Ethics, Satisfaction, BMT.